Eu sou a minha arte: representação social lésbica em Cassandra Rios (1979-1983) - Rodrigues, Amanda Shelle Paula (2024)
This dissertation, titled "I Am My Art: The Social Representation of Lesbianism in Cassandra Rios (1979-1983)," aims to understand the shift in the representation of lesbianism in Cassandra Rios' work "I Am a Lesbian" (1981). The study focuses on identifying and analyzing the social, cultural, and political factors that influenced this change in the author's approach to the subject. To support this analysis, I draw on the theoretical frameworks of Roger Chartier, Antonio Candido, Marco Napolitano, and Renan Quinalha, who provide insights into the relationships between literature, censorship, and the social construction of lesbian identity in Rios' work.